Evidence against β(3)-adrenoceptors or low affinity state of β(1)-adrenoceptors mediating relaxation in rat isolated aorta - Brahmadevara, Nataraj (2003)
1. The presence of β(3)-adrenoceptors and the low affinity state of the β(1)-adrenoceptor (formerly ‘putative β(4)-adrenoceptor') was investigated in ring preparations of rat isolated aorta preconstricted with phenylephrine or prostaglandin F(2α) (PGF(2α)). Relaxant responses to isoprenaline, selective β(3)-adrenoceptor agonists (BRL 37344, SR 58611A, CL 316243) and non-conventional partial agonists (CGP 12177A, cyanopindolol, pindolol) were obtained. 2. In phenylephrine-constricted, but not PGF(2α)-constricted rings, relaxations to isoprenaline showed a propranolol-resistant component. 3. In phenylephrine-constricted rings, relaxations to BRL 37344 (pEC(50), 4.64) and SR 58611A (pEC(50), 4.94) were not antagonized by the selective β(3)-adrenoceptor antagonist SR 59230A (⩽1 μM). CL 316243 (⩽100 μM) failed to produce relaxation. In PGF(2α)-constricted rings only SR 58611A produced relaxation, which was not affected by SR 59230A (⩽3 μM). 4. Non-conventional partial agonists produced relaxation in phenylephrine-constricted but not PGF(2α)-constricted rings. The relaxation to CGP 12177A was unaffected by SR 59230A (⩽1 μM) or by CGP 20712A (10 μM), reported to block the low affinity state of the β(1)-adrenoceptor. 5. β-adrenoceptor antagonists also produced relaxation in phenylephrine-constricted rings with an order of potency of (pEC(50) values): bupranolol (5.5)≈38;SR 59230A (5.47)≈38;cyanopindolol (5.47)>pindolol (5.30)>alprenolol (5.10)>propranolol (4.83)>ICI 118551 (4.60)>CGP 12177A (4.38)≈38;CGP 20712A (4.35). Bupranolol (100 μM), alprenolol (30 μM), propranolol (100 μM) and SR 59230A (10 μM) produced no relaxation in PGF(2α)-constricted rings. 6. These results provide no evidence for the presence of functional β(3)-adrenoceptors or the low affinity state of the β(1)-adrenoceptor in rat aorta.